2014
DOI: 10.17221/7481-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

The effects of in vitro exposure to progesterone and estradiol-17β on the activity of canine neutrophils

Abstract: ABSTRACT:To date, only limited information about the influence of ovarian hormones on canine immune system cells has been available. The study investigated the in vitro influence of progesterone and estradiol-17β on the activity of canine neutrophils. Treatment of cells by both hormones led to a significant decrease in phagocytosisinduced oxidative burst as detected using luminometry after stimulation with opsonised zymosan. The increase in oxidative burst, not connected with phagocytosis, was recorded after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
1
3
0
1
Order By: Relevance
“…) (Marin et al 2010, Bartoskova et al 2014. These observations seem to confirm the research of Doucet et al (2010), who showed a higher activity of neutrophil oxidative burst in rats after ovariectomy than in animals with preserved gonads.…”
Section: Discussionsupporting
confidence: 87%
“…) (Marin et al 2010, Bartoskova et al 2014. These observations seem to confirm the research of Doucet et al (2010), who showed a higher activity of neutrophil oxidative burst in rats after ovariectomy than in animals with preserved gonads.…”
Section: Discussionsupporting
confidence: 87%
“…and oxidative burst [138]. In humans, some authors have shown that mPRα expressed in peripheral blood T cells during pregnancy, is mainly involved in immune response regulation, generates fetal protection and impairs fetal complications [139].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…23 Similarly, this is speculated to occur in pregnant dogs, with steroid hormones suppressing neutrophilic activity. 24 Client education is important to implement hygiene protocols in the household and prevent zoonosis in pets with known infections. Best practices include wearing gloves, frequent hand washing, and isolation from those in the household.…”
Section: Discussionmentioning
confidence: 99%